Performance Analysis of an Ultra Wideband Transceiver for Real-Time Localization - Michler, Fabian; Deniz, Harun; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (2018 48th European Microwave Conference (EuMC), 2018)
In this paper, an ultra wideband localization system based on the DecaWave DW1000 chipset is investigated in detail regarding the achievable precision and accuracy in different measurement scenarios. System parameters, such as channel selection, bandwidth, preamble length and measurement method will be explained in detail and their influence on the localization performance is estimated. Statistically evaluated measurements in different environments with a prototype system consisting of a single anchor and a tag are then used to confirm the theory.<br